Disciplined entrepreneurship : 24 steps to a successful startup - Aulet, Bill, 1958- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2024)
Disciplined Entrepreneurship Expanded and Updated starts by combining the timeless and insightful principles of Disciplined Entrepreneurship with the practical tools found in the Disciplined Entrepreneurship Workbook into a single, comprehensive package. The book also has been updated with recent developments in the field and examples as well as a robust new library of additional resources. Author, entrepreneur, professor, and Managing Director of the Martin Trust Center for MIT Entrepreneurship, Bill Aulet systematically walks readers through exactly how to create a successful startup. This book presents a detailed, sequential but not linear integrated and proven 24-step framework that any entrepreneur can apply immediately to improve their chances of entrepreneurial success. Readers will also find"--
Includes index.
Keywords: New business enterprises -- Management; Nuevas empresas comerciales -- Administración; Entrepreneurship; Emprendimiento